Epistemological foundations of the Islamization of knowledge: a critical comparative study of al-Attas and al-Faruq - Syafe’i, Syafe’i; Riadi, Haris (Jurnal Pendidikan Agama Islam Al-Thariqah, 2026)
This study addresses the ongoing challenge of integrating Islamic principles with modern knowledge by comparing the ideas on the Islamization of knowledge proposed by Syed Muhammad Naquib al-Attas and Isma’il Raji al-Faruqi. It aims to explore their philosophical and methodological orientations and assess their relevance to contemporary knowledge development. Using qualitative literature-based research, the study analyzes primary texts and academic sources through content and comparative analysis. The findings reveal that al-Attas emphasizes epistemological Islamization by purifying key concepts, shaping an Islamic worldview, and highlighting adab as central to resolving the crisis of knowledge, while al-Faruqi adopts a practical-methodological approach by integrating Islamic heritage with modern disciplines through a systematic Workplan for curriculum and institutional reform. Both scholars agree on grounding knowledge in tauhid and rejecting secularization, yet differ in orientation—philosophical versus applied. This study offers novelty by systematically synthesizing both perspectives into a complementary framework for advancing Islamization of knowledge. However, it is limited to a literature-based approach without empirical validation. The findings imply that integrating conceptual and operational strategies is essential for strengthening contemporary Islamic education